Integrasi Tafsir dan Hadis Tarbawi dalam Ilmu Pendidikan Islam - Muhamad Afiffudin; Sultan Arif Fahriansyah; Mungkassifurahman Mungkassifurahman; Maslani Maslani; Opik Taupik Kurahman (Universitas Al Azhar Indonesia, 2026)
This study to analyze the integration of Tafsir and tarbawi hadith in the development of Islamic education. Education in Islam is not only oriented towards the transfer of knowledge, but also towards the formation of morals, spirituality, and character of insan kamil. Tafsir tarbawi plays a role in interpreting verses of the Qur'an related to educational values, while hadith tarbawi provides practical examples of the Prophet Muhammad's educational methods and ethics. This study uses a descriptive qualitative approach through a literature review of relevant primary and secondary sources. The results show that the integration of Tafsir and hadith tarbawi can produce a holistic concept of Islamic education, covering cognitive, affective, and psychomotor aspects. According to Tafsir and tarbawi hadith, the goal of Islamic education is to shape individuals who are faithful, knowledgeable, and pious, who are beneficial to society. In addition, educational evaluation from the perspective of Tafsir and hadith does not only assess the intellectual aspects, but also the moral and spiritual aspects of students. Thus, Tafsir and tarbawi hadith can be used as a normative and methodological basis in designing an Islamic education system that is contextual, humanistic, and oriented towards character building and devotion to Allah SWT. Keywords – Educational Hadith, Educational Interpretation, Integration, Islamic Education.